CAGE15-7 Cruise Report: GEO8144/3144 – Marine Geology and Geophysics Cruise, Greenhouse Gases in the Ocean - Rasmussen, Tine L.; Nielsen, Tove; Kuijpers, Antoon; Sztybor, Kamila; Ezat, Mohamed; Jessen, Simon P.; Dijkstra , Noortje (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
From the late afternoon of July 23rd to the morning of August 3rd, 2015, the Department of Geology Uit, the Arctic University of Norway, arranged a AMGG-Research School scientific teaching cruise aimed atinvestigating the western and northern Svalbard margin and the Barents Sea, the Fram Strait to east Greenland, methane seep sites at Vestnesa, Prins Karls Forland and Storfjorden Trough and on R/V “Helmer Hanssen”. Investigated areas were (in order of visiting sites on the cruise): west of Prins Karls Forland, Vestnesa Ridge, Molloy Deep, Fram Strait, East Greenland margin, Smeerenburgfjorden, Hinlopen, Storfjorden, Storfjorden Trough, and Leirdjupet south of Spitsbergenbanken. The scientific sampling was done within the framework of several ongoing projects at the Department of Geology, University of Tromsø: “CAGE – Centre for Arctic Gashydrate, Environment and Climate”, in which the sub-projects “Paleo-CIRCUS”, “OA-Ocean Acidification” is included. The responsible for this year’s course in GEO8144/GEO3144 is Prof. T.L. Rasmussen. A total of 26 gravity cores, 5 piston cores, 12 plankton net casts and 27 CTD (conductivity-temperature-depth) casts were performed at the planned stations. A total of 86.3 km (46 nm) of airgun surveys were run. 108.97 m mud was obtained in total. Chirp profiles and multibeam lines were acquired during transits and during surveys in Storfjorden, Storfjorden Trough and Leirdjupet. In addition, CTD’s and a small chirp and multibeam survey was performed Storfjorden and in Leirdjupet and airgun lines were run in Storfjorden Trough. The recording of echo-sounding started from c. 78 °N on the shelf outside Isfjorden and ended at c. 72 °N, with pauses when passing through protected areas of Svalbard (Smeerenburgfjorden and Hinlopen and respecting the 12 nm zone in Storfjorden). The cruise may be known as: CAGE15_7_AMGG